CONCEPTS OF RISK MANAGEMENT RESEARCH AS A BASIS FOR UNDERSTANDING THE REDUCTION OF RISK EVENTS OF PHARMACEUTICAL ORGANIZATIONS - Петров, Андрей Георгиевич; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Сашко, Юлия Александровна; Абрамов, Николай Владимирович; Хорошилова, Ольга Владимировна; Марьин, Андрей Александрович (Medicine in Kuzbass, 2022)
The review is devoted to topical issues of the development of the concept of risk management research as a basis for understanding the reduction of risk events of pharmaceutical organizations. The importance of managing risk events in pharmaceutical organizations, which necessitate the improvement of the risk management model, is shown.